Spherical aluminum oxide as well as preparation method and application thereof
By adjusting the pore size distribution of spherical alumina, the problem of too concentrated pore size distribution in the prior art is solved, and the efficient catalytic performance and long life of the catalyst are achieved.
Patent Information
- Application Number
- CN202311420965.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-30
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-10-30
AI Technical Summary
The pore size distribution of existing spherical alumina support is too concentrated, which limits the scope of application and performance of the catalyst.
By adjusting the ratio and grain size of pseudo-thin alumina and thin alumina, spherical alumina is prepared by oil ammonia column forming method, and the pore diameter distribution is controlled to ensure the balance of pore volume and strength.
The efficient catalytic performance of the catalyst is achieved, the reaction activity and product selectivity are improved, the service life of the catalyst is extended, and the production cost is reduced.
Smart Images

Figure BDA0004521076280000261 
Figure BDA0004521076280000262 
Figure BDA0004521076280000271
Abstract
Description
Technical Field
[0001] The invention relates to the field of spherical alumina preparation, and in particular to spherical alumina and a preparation method and application thereof. Background Art
[0002] Activated alumina has suitable pore distribution, good adsorption, thermal stability, surface acidity and large specific surface area. It is one of the most widely used industrial catalyst carriers. In different industrial applications, the shape and requirements of alumina carriers vary according to the different processes used in the industrial process. For the moving bed process of continuous reforming, the alumina carrier used in its catalyst needs to be prepared into a regular sphere in order to reduce the mechanical wear caused by the continuous transportation and recycling of the catalyst during the industrial production process. Since the 1990s, people have conducted a lot of research on the preparation method of spherical alumina. At present, the more mature methods include rotation spheroidization, spray granulation spheroidization and oil column spheroidization. Among them, oil column spheroidization is divided into two methods: hot oil column molding and oil ammonia column molding.
[0003] Oil column molding is the main preparation method for spherical alumina carriers used in moving bed catalysts. Compared with methods such as rotating spheres, it has the characteristics of high sphericity and uniform particle size of the prepared alumina spheres. For oil-ammonia column molding, aluminum hydroxide (pseudo-boehmite or boehmite) is generally used as the raw material, and an appropriate amount of acid is added and fully stirred to obtain an alumina sol, which is then dripped into the oil-ammonia column for molding. The upper layer of the oil-ammonia column is the oil layer, and the lower layer is the ammonia water layer. The main function of the oil layer is to make the dripped alumina sol spherical. The surface tension of the selected oil and sol should be large enough to ensure that the dripped sol droplets have good sphericity; the interfacial tension between the ammonia water layer and the oil layer should be small enough to allow the sol spheres formed in the oil layer to smoothly enter the ammonia water layer without deformation; the aluminum hydroxide sol spheres are solidified in ammonia water and become gel spheres, which are then washed, dried, and calcined to obtain spherical alumina carrier products.
[0004] In the preparation process of the moving bed catalyst for continuous reforming, the properties of the spherical alumina carrier directly determine the performance of the catalyst. The spherical alumina carrier needs to have a large specific surface area so that the active metal Pt can be highly dispersed; secondly, the spherical alumina also needs to have a large pore volume to increase the carbon capacity of the catalyst and reduce the deactivation rate of the catalyst; it needs to have sufficient strength and hydrothermal stability to resist mechanical and thermal shocks during the reaction and regeneration process and extend the service life of the catalyst; in addition, the catalyst also needs to have a suitable stacking density. The appropriate stacking density allows a lower catalyst loading to be obtained under the premise of achieving the catalytic reaction effect and process requirements, reducing the total amount of catalyst and the total platinum amount of platinum-containing precious metal catalysts, saving investment costs. In recent years, researchers have found that the pore structure of the spherical alumina carrier, that is, the pore size distribution, also has a significant effect on the performance of the catalyst. A larger pore diameter is conducive to increasing the diffusion rate of reactant and product molecules during the reaction and improving the reaction efficiency, but too large a pore size will lead to a decrease in the strength of the catalyst. In order to maintain a large specific surface area and high strength, a certain proportion of small pores needs to be retained in the spherical alumina. Therefore, in recent years, the preparation of spherical alumina carriers with large specific surface area and suitable pore diameter distribution has attracted more and more attention.
[0005] CN104148117A discloses a method for preparing an alumina carrier and a catalyst. Two types of boehmite with different grain sizes are used as raw materials to prepare an alumina carrier, and the specific surface area thereof measured by nitrogen adsorption method is 180 to 250 m 2 / g, pore volume is 0.40-0.8mL / g, wherein the pore distribution measured by nitrogen adsorption method is: the proportion of pores with diameters of 4-6nm to the total pore volume is 6.0-11.0%, the proportion of pores with diameters of 6-20nm to the total pore volume is 88-92%, and the proportion of pores with diameters greater than 20nm to the total pore volume is 0.2-2.0%. The catalyst prepared from the carrier is used for naphtha catalytic reforming reaction, has low carbon deposition, and has good strength.
[0006] CN107837797A discloses an alumina ball with a bimodal pore distribution and a preparation method thereof. Pseudo-boehmite, aluminum sol and water are mixed and peptized to obtain aluminum hydroxide sol, wherein the aluminum sol has an aluminum / chlorine mass ratio of 1.0 to 1.4. The obtained aluminum hydroxide sol is mixed with a gelling agent solution and then dripped into a hot oil column to form a ball. The formed ball is taken out, washed, dried and calcined after aging to obtain an alumina ball. The pore diameter of the alumina ball shows obvious bimodal peaks at 4 to 10 nm and 12 to 20 nm. When the alumina ball is used for the preparation of a continuous reforming catalyst, the catalyst has a higher aromatic yield.
[0007] CN115448338A discloses a macroporous spherical alumina and its preparation method: using pseudo-boehmite as raw material, forming gel spheres through oil-ammonia column, then placing the gel spheres in fatty alcohol for aging, and then drying and calcining to obtain macroporous spherical alumina. The spherical alumina carrier has a diameter of 200-240 m 2 / g specific surface area, 0.7~0.9cm 3 / g of pore volume, of which pores with a pore diameter less than 6nm account for 0-2% of the total pore volume, pores with a pore diameter of 6-10nm account for 4-12% of the total pore volume, pores with a pore diameter of 10-20nm account for 86-95% of the total pore volume, and pores with a pore diameter greater than 20nm account for 0.1-3% of the total pore volume. The macroporous spherical alumina has a large pore volume, and the macropore distribution is relatively concentrated. The method uses aluminum hydroxide gel balls to expand the pores by aging in an organic solvent, and does not allow the use of a pore expanding agent, thereby reducing the discharge of three wastes in the production process and reducing the production cost of the spherical alumina carrier.
[0008] In the spherical alumina carrier prepared by the prior art, the pore diameter distribution is mainly concentrated in the range of 6 to 20 nm, which is relatively narrow, limiting the application scope of some catalysts prepared using this as the carrier and affecting the catalytic performance of the catalyst. Summary of the invention
[0009] The purpose of the present invention is to overcome the problems existing in the existing spherical alumina and provide a spherical alumina and its preparation method and application. The spherical alumina of the present invention has a suitable pore structure and can be used as a catalyst carrier to significantly improve the catalytic performance of the catalyst.
[0010] In order to achieve the above objectives, the first aspect of the present invention provides a spherical alumina, in which pores with a pore diameter of 6-10 nm account for 10-22% of the total pore volume, pores with a pore diameter of 10-20 nm account for 50-75% of the total pore volume, and pores with a pore diameter of 20-50 nm account for 10-25% of the total pore volume.
[0011] Preferably, there are no pores with a pore diameter less than 6 nm in the spherical alumina.
[0012] Preferably, in the spherical alumina, pores with a pore diameter greater than 50 nm account for less than 5% of the total pore volume.
[0013] A second aspect of the present invention provides a method for preparing spherical alumina, the method comprising the following steps:
[0014] (1) peptizing pseudo-boehmite and boehmite to obtain aluminum hydroxide slurry;
[0015] (2) dropping aluminum hydroxide slurry into an oil-ammonia column to form wet aluminum hydroxide pellets, and then drying and calcining the wet aluminum hydroxide pellets;
[0016] Wherein, the grain size of the boehmite meets: D (200) / D (002) =0.5-1.5, D (200) / D (020) =0.7-1.5, wherein the D (020) , D (200) and D (002) are the grain sizes calculated by the Scherrer formula based on the half-width of the diffraction peaks along the (020) crystal plane, (200) crystal plane and (002) crystal plane in the X-ray diffraction curve of boehmite;
[0017] Among them, in the pseudo-boehmite, D (120) Less than 10 nm, wherein the D (120) is the crystallite size calculated by the Scherrer formula based on the half-peak width of the diffraction peak along the (120) crystal plane in the X-ray diffraction curve of pseudo-boehmite;
[0018] Wherein, based on the total dry mass of pseudo-boehmite and boehmite, the dry mass content of pseudo-boehmite is 20-50%, and the dry mass content of boehmite is 50-80%.
[0019] Preferably, the particle size of the boehmite is 0.1-500 μm, preferably 0.1-400 μm.
[0020] Preferably, the D of the boehmite 50 It is 40-200 μm, preferably 40-100 μm.
[0021] Preferably, the particle size of the pseudo-boehmite is 0.1-300 μm, preferably 0.5-200 μm.
[0022] Preferably, the D of the pseudo-boehmite 50 5-60 μm, preferably 30-60 μm.
[0023] The third aspect of the present invention provides a use of the spherical alumina described in the first aspect or the spherical alumina prepared by the method described in the second aspect in catalyst preparation.
[0024] Through the above technical solution, the beneficial effects of the present invention include:
[0025] The spherical alumina of the present invention has a suitable pore structure and can be used as a catalyst carrier to significantly improve the catalytic performance of the catalyst, and at the same time can improve the carbon holding capacity of the catalyst during the reaction process, slow down the deactivation rate of the catalyst, and increase the service life of the catalyst. When the catalyst prepared by using the spherical alumina of the present invention as a carrier is used in the field of continuous reforming, it is beneficial to improve the reaction activity and product selectivity. DETAILED DESCRIPTION
[0026] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0027] The first aspect of the present invention provides a spherical alumina, in which pores with a pore diameter of 6-10 nm account for 10-22% of the total pore volume, pores with a pore diameter of 10-20 nm account for 50-75% of the total pore volume, and pores with a pore diameter of 20-50 nm account for 10-25% of the total pore volume.
[0028] It should be noted that, in the spherical alumina of the present invention, the pore diameter endpoint of 10 nm is included in pores with a pore diameter of 10-20 nm, and the pore diameter endpoint of 20 nm is included in pores with a pore diameter of 20-50 nm.
[0029] According to the present invention, preferably, in the spherical alumina, pores with a pore diameter of 6-10 nm account for 12-22% of the total pore volume, pores with a pore diameter of 10-20 nm account for 55-75% of the total pore volume, and pores with a pore diameter of 20-50 nm account for 10-20% of the total pore volume. By using this preferred embodiment as a carrier, the catalytic performance of the catalyst can be further improved. When it is applied to the field of continuous reforming, it is beneficial to improve the yield of aromatics.
[0030] According to the present invention, preferably, there are no pores with a pore diameter less than 6 nm in the spherical alumina. With this preferred embodiment, the pore diameter of the spherical alumina is controlled at a relatively large level, which is conducive to improving the utilization rate of active metals.
[0031] According to the present invention, preferably, in the spherical alumina, pores with a pore diameter greater than 50 nm account for less than 5% of the total pore volume. With this preferred embodiment, the pore diameter of the spherical alumina is controlled to be mainly distributed in the range of 10-50 nm, which is conducive to ensuring that the spherical alumina carrier has a higher strength while maintaining a higher pore volume.
[0032] The pore size distribution, specific surface area and pore volume of the spherical alumina described in the present invention are measured using the Autosorb-6B fully automatic specific surface area and porosity analyzer of the American Quantachrome Company. Determination method: Before the test, the alumina ball sample is vacuum degassed at 1.33Pa and 300°C for 4 hours, and then isothermally adsorbed and desorbed at a liquid nitrogen temperature of 77.4K (-196°C) using high-purity nitrogen as the adsorption medium, and the isotherm is measured; the specific surface area is calculated using the BET (Brunauer-Emmett-Teller) equation, and the pore volume and pore size distribution are calculated from the desorption isotherm using the BJH equivalent cylinder model.
[0033] According to the present invention, preferably, the spherical alumina is γ-alumina. This preferred embodiment is applied to the continuous reforming process, which is more conducive to improving the yield of aromatics.
[0034] The crystal structure of the spherical aluminum oxide of the present invention is measured by X-ray diffraction (XRD).
[0035] According to the present invention, preferably, the specific surface area of the spherical alumina is 190-230m 2 / g.
[0036] According to the present invention, preferably, the pore volume of the spherical alumina is 0.6-0.9 cm 3 / g.
[0037] According to the present invention, preferably, the average particle size of the spherical alumina is 1.4-1.8 mm.
[0038] The spherical alumina of the present invention has a relatively suitable specific surface area, pore volume and average particle size. When the catalyst prepared by using the spherical alumina as a carrier is used in the field of continuous reforming, it is beneficial to improve the reaction activity and product selectivity.
[0039] According to the present invention, preferably, the sphericity of the spherical alumina is greater than 0.95.
[0040] According to the present invention, preferably, the Q of the spherical alumina 0.95 Greater than 95% by volume, wherein Q 0.95 It is the volume proportion of spherical alumina particles with a sphericity greater than 0.95 in all spherical alumina particles.
[0041] The sphericity of the spherical alumina described in the present invention and the above-mentioned average particle size are measured using the CAMSIZER multifunctional particle size analyzer of the German RETSCH company. The ideal sphericity of alumina spheres is 1. Under normal circumstances, the sphericity of alumina spheres is less than 1. Sphericity measurement of the spherical alumina described in the present invention: the average value of the sphericity of the particles in the 50mL sample. The proportion (volume) of particles with a sphericity (SPHT) greater than 0.95 in the alumina sphere sample is measured using Q 0.95 express.
[0042] According to the present invention, preferably, the crushing strength of the spherical alumina is 45-80N / grain.
[0043] The crushing strength of the spherical alumina described in the present invention is measured by a DL4 type (produced by Dalian Penghui Technology Development Co., Ltd.) particle strength tester. Determination method: Dry the alumina balls at 120°C for 2 hours, put them in a dryer and cool them to 25°C, and take out 50 ball samples to be tested. Set the relevant measurement parameters of the particle strength tester, place a tested alumina ball sample on the sample table, click the measurement button, and the force rod slowly falls to increase the pressure until the ball sample to be measured is broken, and record the pressure data. Among the pressure data of the 50 balls measured, exclude a maximum value and a minimum value, and take the average value of the other data, which is the crushing strength of the tested ball sample.
[0044] The spherical alumina provided by the present invention has high sphericity and strength, can further improve the carbon holding capacity of the catalyst during the reaction process, reduce the breakage rate of the catalyst during the continuous reaction process, reduce the loss of the catalyst, and extend the service life of the catalyst.
[0045] A second aspect of the present invention provides a method for preparing spherical alumina, the method comprising the following steps:
[0046] (1) peptizing pseudo-boehmite and boehmite to obtain aluminum hydroxide slurry;
[0047] (2) dropping aluminum hydroxide slurry into an oil-ammonia column to form wet aluminum hydroxide pellets, and then drying and calcining the wet aluminum hydroxide pellets;
[0048] Wherein, the grain size of the boehmite meets: D (200) / D (002) =0.5-1.5, D (200) / D (020) =0.7-1.5, wherein the D (020) , D (200) and D (002)are the grain sizes calculated by the Scherrer formula based on the half-width of the diffraction peaks along the (020) crystal plane, (200) crystal plane and (002) crystal plane in the X-ray diffraction curve of boehmite;
[0049] Among them, in the pseudo-boehmite, D (120) Less than 10 nm, wherein the D (120) is the crystallite size calculated by the Scherrer formula based on the half-peak width of the diffraction peak along the (120) crystal plane in the X-ray diffraction curve of pseudo-boehmite;
[0050] Wherein, based on the total dry mass of pseudo-boehmite and boehmite, the dry mass content of pseudo-boehmite is 20-50%, and the dry mass content of boehmite is 50-80%.
[0051] The preparation method provided by the present invention adopts a specific ratio of pseudo-boehmite with a specific grain size to be combined with boehmite, and then the spherical alumina with a suitable pore structure as described in the first aspect can be obtained by an oil-ammonia column spheroidization method, which is used as a catalyst carrier to improve the catalytic performance of the catalyst. When the catalyst prepared by using the spherical alumina as a carrier is used in the field of continuous reforming, it is beneficial to improve the yield of aromatics.
[0052] In the present invention, the specific definitions of pseudo-boehmite and boehmite are well known to those skilled in the art, and will not be described in detail herein.
[0053] According to the present invention, preferably, the grain size of the boehmite meets the following requirements: (200) / D (002) =0.6-1.3, D (200) / D (020) =0.8-1.5, wherein the D (020) , D (200) and D (002) are the grain sizes calculated by the Scherrer formula based on the half-peak widths of the diffraction peaks along the (020) crystal plane, (200) crystal plane and (002) crystal plane in the X-ray diffraction curve of boehmite. The use of boehmite with the above block structure is more conducive to obtaining the spherical alumina with a suitable pore structure described in the present invention.
[0054] According to the present invention, preferably, the particle size of the boehmite is 0.1-500 μm, preferably 0.1-400 μm.
[0055] According to the present invention, preferably, the D of the boehmite 50It is 40-200μm, preferably 40-100μm, for example, it can be 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm, 200μm, and any value in the range formed by any two of these values.
[0056] Controlling the macroscopic particle size of boehmite within the above range is beneficial to obtaining the spherical alumina having the pore structure described in the first aspect of the present invention, while increasing the pore volume of the spherical alumina.
[0057] According to the present invention, preferably, in the pseudo-boehmite, D (120) Less than 6 nm, for example, 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 5.5 nm, and any value in the range formed by any two of these values, wherein the D (120) The crystal size is calculated by the Scherrer formula based on the half-width of the diffraction peak along the (120) crystal plane in the X-ray diffraction curve of pseudo-boehmite. The use of the pseudo-boehmite with small crystal grains is conducive to obtaining the spherical alumina with the pore structure described in the first aspect of the present invention, and is also conducive to improving the strength of the spherical alumina.
[0058] According to the present invention, preferably, the particle size of the pseudo-boehmite is 0.1-300 μm, preferably 0.5-200 μm.
[0059] According to the present invention, preferably, the D of the pseudo-boehmite 50 It is 5-60 μm, preferably 30-60 μm, for example, it can be 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, and any value in the range formed by any two of these values.
[0060] Controlling the macroscopic particle size of pseudo-boehmite within the above range is beneficial to obtaining the spherical alumina having the pore structure described in the first aspect of the present invention, and is also beneficial to improving the strength of the spherical alumina.
[0061] The present invention has no particular limitation on the sources of the pseudo-boehmite and boehmite, which can be purchased commercially or prepared by conventional methods in the art.
[0062] In the present invention, based on the total dry weight of pseudo-boehmite and boehmite, the dry weight content of pseudo-boehmite is 20-50%, preferably 20-40%, such as 20%, 25%, 30%, 35%, 40%, 45%, 50%, and any value in the range formed by any two of these values; the dry weight content of boehmite is 50-80%, preferably 60-80%, such as 50%, 55%, 60%, 65%, 70%, 75%, 80%, and any value in the range formed by any two of these values. Using pseudo-boehmite and boehmite in a specific ratio is conducive to forming spherical alumina with the special pore structure described in the first aspect.
[0063] The present invention has a wide range of acid types for the peptization in step (1), which can be a conventional choice in the art. Preferably, the acid used in the peptization in step (1) is an inorganic acid and / or an organic acid, wherein the inorganic acid is nitric acid and / or hydrochloric acid, and the organic acid is selected from at least one of trichloroacetic acid, formic acid and citric acid.
[0064] According to the present invention, preferably, the ratio of the mass of the acid used for the peptization in step (1) to the total mass of pseudo-boehmite and boehmite calculated as alumina is 0.01-0.1, preferably 0.01-0.08.
[0065] According to the present invention, preferably, the acid used for the peptization in step (1) is provided in the form of an acid solution, and the concentration of the acid solution is 0.1-2 mol / L, preferably 0.1-1.5 mol / L.
[0066] The present invention has no particular limitation on the peptization process of step (1), and it can be carried out according to conventional methods in the art. Preferably, the peptization time of step (1) is 0.5-20 hours.
[0067] Preferably, the peptization in step (1) is carried out under stirring.
[0068] The present invention has no particular limitation on the stirring rate, which can be appropriately selected according to the specific situation, so as to ensure uniform mixing. Preferably, the stirring rate is 60-300 rpm.
[0069] Preferably, water is also added during the peptization process in step (1).
[0070] The present invention has no particular limitation on the amount of water used, provided that the solid content of the aluminum hydroxide slurry is within the following range.
[0071] According to the present invention, preferably, the solid content of the aluminum hydroxide slurry obtained in step (1) is 15-28% by weight, preferably 15-25% by weight, and more preferably 18-22% by weight.
[0072] According to the present invention, preferably, the oil-ammonia column comprises an organic phase and an aqueous ammonia phase, and the height ratio of the organic phase to the aqueous ammonia phase is 1:5-300, preferably 1:5-200.
[0073] Preferably, the height of the aqueous ammonia phase is 100-300 cm.
[0074] The present invention has no particular limitation on the specific type of the organic phase, which can be selected conventionally in the art. Preferably, the organic phase is C5-C 20 The alkane is preferably at least one selected from gasoline, kerosene, petroleum ether, n-pentane, n-hexane, n-heptane, n-octane, n-decane and undecane.
[0075] According to the present invention, preferably, the concentration of the aqueous ammonia is 6-18% by weight, preferably 5-15% by weight.
[0076] The present invention has no particular limitation on the process of preparing wet aluminum hydroxide pellets, and the process can be carried out in accordance with conventional methods in the art. Preferably, the process of dripping aluminum hydroxide slurry into a pelletizing column to prepare wet aluminum hydroxide pellets in step (1) comprises dripping aluminum hydroxide slurry into an organic phase of a pelletizing column to form pellets, and then entering an ammonia aqueous phase to solidify for 1-10 hours to form wet aluminum hydroxide pellets.
[0077] Specifically, the process of dripping aluminum hydroxide slurry into a ball-forming column to form wet aluminum hydroxide balls in step (2) includes: dripping aluminum hydroxide slurry into the upper layer of the oil-ammonia column using a ball dropper, and due to the effect of surface tension, the droplets shrink into a ball shape when passing through the upper organic phase layer, pass through the interface between the oil phase and the ammonia water phase, and enter the ammonia water to gel. The gelled particles are solidified in the ammonia water phase of the lower layer of the oil-ammonia column for 1-10 hours to become wet aluminum hydroxide balls (i.e., gel balls in the embodiment), which are collected at the bottom of the oil-ammonia column.
[0078] The present invention has no particular limitation on the drying in step (2), and the drying can be carried out according to the commonly used methods in the art. Preferably, the drying conditions in step (2) include: a temperature of 50-150° C. and a time of 5-24 hours.
[0079] Further preferably, the drying conditions in step (2) include: first drying at 50-80° C. for 2-8 hours, and then drying at 90-150° C. for 6-12 hours.
[0080] According to the present invention, preferably, the calcination conditions in step (2) include: a temperature of 450-800° C. and a time of 2-8 hours.
[0081] The third aspect of the present invention provides an application of the spherical alumina described in the first aspect or the spherical alumina prepared by the method described in the second aspect in catalyst preparation, preferably in the preparation of continuous reforming catalyst.
[0082] The spherical alumina provided by the present invention is suitable for being used as a catalyst carrier, and is preferably suitable for being used as a carrier of a continuous reforming catalyst.
[0083] Preferably, the active components of the continuous reforming catalyst are selected from noble metals and / or Group VIII metals.
[0084] The present invention will be described in detail below through examples.
[0085] In the following examples, the test methods for pore size distribution, specific surface area, pore volume, sphericity, crushing strength, and average particle size of spherical alumina were performed according to the test methods given above;
[0086] Grain size test method of boehmite and pseudo-boehmite: XRD diffraction curve is measured by Philips X'pert X-ray diffractometer, using Cu target, Kα radiation, Ni filter, λ=0.154056nm. Solid detector, tube voltage 40kV, tube current 40mA, scanning range 5°-90°, and then calculated according to Scherrer formula: D=Kλ / (Bcosθ) (D is grain size, λ is the diffraction wavelength of target material, B is the half-peak width of the corrected diffraction peak, 2θ is the position of the diffraction peak);
[0087] The particle size distribution of pseudo-boehmite and boehmite was measured using BetterSize2000 laser scattering instrument from Dandong Better Technology Co., Ltd. The measurement method is as follows: set the particle refractive index: 1.530; particle absorption rate: 0.1; dispersant: water; dispersant refractive index: 1.330; instrument range: 20nm-2mm. Click on automatic calibration, and after the instrument is calibrated, add the sample to be tested into the sample slot. When the concentration reaches the measurement requirement, stop adding, and the instrument will automatically detect. After the detection is completed, record the measured particle size distribution and D 50 value.
[0088] Example 1
[0089] (1) Preparation of pseudo-boehmite and boehmite
[0090] In a three-necked flask with a reflux condenser, add 54 grams of aluminum chips with a purity of 99.95wt% and 180mL (1.4mol) of n-hexanol with a purity of 99.8wt%. Reflux at 130°C for 20min to start the reaction. Continue to slowly add 724mL (5.8mol) of n-hexanol into the three-necked flask, maintain the temperature at 140°C, and reflux for 2h to obtain a mixture of n-hexyl aluminum and n-hexanol.
[0091] The mixture of n-hexyl aluminum and n-hexanol was cooled to 90°C, and 936g of deionized water was added thereto at a stirring speed of 120rpm for hydrolysis. The hydrolysis time was 30min, and a two-phase system with an upper n-hexanol phase and a lower aluminum hydroxide slurry phase was obtained. The n-hexanol phase of the upper layer was separated by decantation to obtain an aluminum hydroxide slurry without alcohol. The aluminum hydroxide slurry was directly spray-dried at 180°C to obtain pseudo-boehmite powder. Its characteristic parameters are shown in Table 1.
[0092] Aluminum hydroxide slurry was prepared by the same method as above, and a grain structure regulator consisting of 12g of 2-hydroxypropionic acid and 28g of n-hexanol was added to the aluminum hydroxide slurry. After stirring evenly, the aluminum hydroxide slurry was transferred to a stainless steel autoclave with adjustable speed mechanical stirring, and aged for 6h at 120°C and a stirring rate of 200rpm. After aging, the slurry was washed with deionized water, and then placed in an oven at 120°C for 12h, and then ground to obtain boehmite powder. Its characteristic parameters are shown in Table 1.
[0093] (2) Preparation of aluminum hydroxide sol
[0094] Take 30g (dry basis mass of alumina) of the pseudo-boehmite powder prepared above and 70g (dry basis mass of alumina) of boehmite powder, add 265ml of 0.19mol / L nitric acid solution for peptization, then add deionized water to a total mass of 396g, disperse and peptize for 3 hours at a stirring rate of 300r / min to obtain an aluminum hydroxide sol with a solid content of 20wt%.
[0095] (3) Preparation of alumina balls
[0096] The aluminum hydroxide sol prepared in step (2) is dripped into the oil-ammonia column with a ball dropper. The upper layer of the oil-ammonia column is the oil phase and the lower layer is the ammonia water phase. The upper oil phase is 1 cm high n-decane and the lower ammonia water phase is 150 cm high ammonia water with a concentration of 8% by weight. The aluminum hydroxide sol is dripped into the oil layer and shrinks into a spherical shape under the action of surface tension. It passes through the interface between the oil phase and the ammonia water phase and enters the ammonia water to gel. The gelled particles are further solidified in the ammonia water phase in the lower layer of the oil-ammonia column for 2 hours to form gel beads, which are collected at the bottom of the oil-ammonia column. The obtained gel beads are taken out from the bottom of the oil-ammonia column, dried at 60°C for 3 hours and 120°C for 9 hours, and then calcined at 600°C for 6 hours to obtain γ-Al2O3 beads A with a ball yield of 97.8% by weight.
[0097] The pore diameter distribution of γ-Al2O3 ball A is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.
[0098] Example 2
[0099] (1) Preparation of pseudo-boehmite and boehmite
[0100] In a three-necked flask with a reflux condenser, add 54 grams of aluminum chips with a purity of 99.95wt% and 180mL (1.4mol) of n-hexanol with a purity of 99.8wt%. Reflux at 130°C for 20min to start the reaction. Continue to slowly add 724mL (5.8mol) of n-hexanol into the three-necked flask, maintain the temperature at 140°C, and reflux for 2h to obtain a mixture of n-hexyl aluminum and n-hexanol.
[0101] The mixture of n-hexyl aluminum and n-hexanol was cooled to 90°C, and 936g of deionized water was added thereto at a stirring speed of 120rpm for hydrolysis. The hydrolysis time was 30min, and a two-phase system with an upper n-hexanol phase and a lower aluminum hydroxide slurry phase was obtained. The n-hexanol phase of the upper layer was separated by decantation to obtain an aluminum hydroxide slurry without alcohol. The aluminum hydroxide slurry was directly spray-dried at 180°C to obtain pseudo-boehmite powder. Its characteristic parameters are shown in Table 1.
[0102] Aluminum hydroxide slurry was prepared by the same method as above, and a grain structure regulator consisting of 12g of 2-hydroxypropionic acid and 28g of n-hexanol was added to the aluminum hydroxide slurry. After stirring evenly, the aluminum hydroxide slurry was transferred to a stainless steel autoclave with adjustable speed mechanical stirring, and aged for 6h at 120°C and a stirring rate of 200rpm. After aging, the slurry was washed with deionized water, and then placed in an oven at 120°C for 12h, and then ground to obtain boehmite powder. Its characteristic parameters are shown in Table 1.
[0103] (2) Preparation of aluminum hydroxide sol
[0104] Take 20g (dry basis mass of alumina) of the pseudo-boehmite powder prepared above and 80g (dry basis mass of alumina) of boehmite powder, add 267ml of 0.19mol / L nitric acid solution for peptization, then add deionized water to a total mass of 399g, disperse and peptize for 6 hours at a stirring rate of 100r / min to obtain an aluminum hydroxide sol with a solid content of 20wt%.
[0105] (3) Preparation of alumina balls
[0106] The aluminum hydroxide sol prepared in step (2) is dripped into the oil-ammonia column with a ball dropper. The upper layer of the oil-ammonia column is the oil phase and the lower layer is the ammonia water phase. The upper oil phase is n-octane with a height of 2 cm, and the lower ammonia water phase is ammonia water with a concentration of 8% by weight and a height of 200 cm. The aluminum hydroxide sol is dripped into the oil layer and shrinks into a sphere under the action of surface tension. It passes through the interface between the oil phase and the ammonia water phase and enters the ammonia water to gel. The gelled particles are further solidified in the ammonia water phase in the lower layer of the oil-ammonia column for 2 hours to form gel beads, which are collected at the bottom of the oil-ammonia column. The obtained gel beads are taken out from the bottom of the oil-ammonia column, dried at 60°C for 3 hours, dried at 120°C for 9 hours, and then calcined at 600°C for 6 hours to obtain γ-Al2O3 beads B, with a ball yield of 97% by weight.
[0107] The pore diameter distribution of γ-Al2O3 ball B is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.
[0108] Example 3
[0109] (1) Preparation of pseudo-boehmite and boehmite
[0110] In a three-necked flask with a reflux condenser, add 54 grams of aluminum chips with a purity of 99.95wt% and 180mL (1.4mol) of n-hexanol with a purity of 99.8wt%. Reflux at 130°C for 20min to start the reaction. Continue to slowly add 724mL (5.8mol) of n-hexanol into the three-necked flask, maintain the temperature at 140°C, and reflux for 2hr to obtain a mixture of n-hexyl aluminum and n-hexanol.
[0111] The mixture of n-hexyl aluminum and n-hexanol was cooled to 90°C, and 936g of deionized water was added thereto at a stirring speed of 120rpm for hydrolysis. The hydrolysis time was 30min, and a two-phase system with an upper n-hexanol phase and a lower aluminum hydroxide slurry phase was obtained. The n-hexanol phase of the upper layer was separated by decantation to obtain an aluminum hydroxide slurry without alcohol. The aluminum hydroxide slurry was directly spray-dried at 180°C to obtain pseudo-boehmite powder. Its characteristic parameters are shown in Table 1.
[0112] Aluminum hydroxide slurry was prepared by the same method as above, and a grain structure regulator consisting of 6 g of 2-hydroxypropionic acid and 14 g of n-hexanol was added to the aluminum hydroxide slurry. After stirring evenly, the aluminum hydroxide slurry was transferred to a stainless steel autoclave with adjustable speed mechanical stirring, and aged for 10 h at 120° C. and a stirring rate of 200 rpm. After aging, the slurry was washed with deionized water, and then placed in an oven at 120° C. for 12 h, and then ground to obtain boehmite powder. Its characteristic parameters are shown in Table 1.
[0113] (2) Preparation of aluminum hydroxide sol
[0114] Take 40g (dry basis mass of alumina) of the pseudo-boehmite powder and 60g (dry basis mass of alumina) of boehmite powder prepared above, add 263ml of 0.19mol / L nitric acid solution for peptization, then add deionized water to a total mass of 393g, disperse and peptize for 1 hour at a stirring rate of 300r / min to obtain an aluminum hydroxide sol with a solid content of 20wt%.
[0115] (3) Preparation of alumina balls
[0116] The aluminum hydroxide sol prepared in step (2) is dripped into the oil-ammonia column with a ball dropper. The upper layer of the oil-ammonia column is the oil phase, and the lower layer is the ammonia water phase. The upper oil phase is n-octane with a height of 1 cm, and the lower ammonia water phase is ammonia water with a concentration of 8% by weight and a height of 200 cm. The aluminum hydroxide sol is dripped into the oil layer, shrinks into a sphere under the action of surface tension, passes through the interface between the oil phase and the ammonia water phase, and enters the ammonia water to gel. The gelled particles are further solidified in the ammonia water phase in the lower layer of the oil-ammonia column for 2 hours to form gel beads, which are collected at the bottom of the oil-ammonia column. The obtained gel beads are taken out from the bottom of the oil-ammonia column, dried at 60°C for 3 hours, dried at 120°C for 9 hours, and then calcined at 600°C for 6 hours to obtain γ-Al2O3 beads C, with a ball yield of 97.5% by weight.
[0117] The pore diameter distribution of γ-Al2O3 ball C is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.
[0118] Example 4
[0119] (1) Preparation of pseudo-boehmite and boehmite
[0120] In a three-necked flask with a reflux condenser, 54 g of aluminum chips with a purity of 99.95 wt% and 180 mL (1.4 mol) of n-hexanol with a purity of 99.8 wt% were added. The reaction began after reflux at 130°C for 20 min. 724 mL (5.8 mol) of n-hexanol was slowly added to the three-necked flask, the temperature was maintained at 140°C, and refluxed for 2 h to obtain a mixture of n-hexyl aluminum and n-hexanol.
[0121] The mixture of n-hexyl aluminum and n-hexanol was cooled to 80°C, and 936 g of deionized water was added thereto at a stirring speed of 120 rpm for hydrolysis. The hydrolysis time was 10 min, and a two-phase system with an upper n-hexanol phase and a lower aluminum hydroxide slurry phase was obtained. The n-hexanol phase of the upper layer was separated by decantation to obtain an aluminum hydroxide slurry without alcohol. The aluminum hydroxide slurry was directly spray-dried at 200°C to obtain pseudo-boehmite powder. Its characteristic parameters are shown in Table 1.
[0122] Aluminum hydroxide slurry was prepared by the same method as above, and a grain structure regulator consisting of 6 g of 2-hydroxypropionic acid and 14 g of n-hexanol was added to the aluminum hydroxide slurry. After stirring evenly, the aluminum hydroxide slurry was transferred to a stainless steel autoclave with adjustable speed mechanical stirring, and aged for 10 h at 120° C. and a stirring rate of 200 rpm. After aging, the slurry was washed with deionized water, and then placed in an oven at 120° C. for 12 h, and then ground to obtain boehmite powder. Its characteristic parameters are shown in Table 1.
[0123] (2) Preparation of aluminum hydroxide sol
[0124] Take 25g (dry basis mass of alumina) of the pseudo-boehmite powder prepared above and 75g (dry basis mass of alumina) of boehmite powder, add 266ml of 0.19mol / L nitric acid solution for peptization, then add deionized water to a total mass of 397.5g, disperse and peptize for 3 hours at a stirring rate of 300r / min to obtain an aluminum hydroxide sol with a solid content of 20wt%.
[0125] (3) Preparation of alumina balls
[0126] The aluminum hydroxide sol prepared in step (2) is dripped into the oil-ammonia column with a ball dropper. The upper layer of the oil-ammonia column is the oil phase, and the lower layer is the ammonia water phase. The upper oil phase is 1 cm high n-decane, and the lower ammonia water phase is 300 cm high ammonia water with a concentration of 8% by weight. The aluminum hydroxide sol is dripped into the oil layer, shrinks into a sphere under the action of surface tension, passes through the interface between the oil phase and the ammonia water phase, and enters the ammonia water to gel. The gelled particles are further solidified in the ammonia water phase in the lower layer of the oil-ammonia column for 6 hours to form gel beads, which are collected at the bottom of the oil-ammonia column. The obtained gel beads are taken out from the bottom of the oil-ammonia column, dried at 60°C for 3 hours, dried at 120°C for 9 hours, and then calcined at 600°C for 6 hours to obtain γ-Al2O3 beads D, with a ball yield of 97.8% by weight.
[0127] The pore diameter distribution of γ-Al2O3 ball D is shown in Table 1, and other physical and chemical properties and crushing strength are shown in Table 2.
[0128] Example 5
[0129] (1) Preparation of pseudo-boehmite and boehmite
[0130] In a three-necked flask with a reflux condenser, 54 g of aluminum chips with a purity of 99.95 wt% and 180 mL (1.4 mol) of n-hexanol with a purity of 99.8 wt% were added. The reaction began after reflux at 130°C for 20 min. 724 mL (5.8 mol) of n-hexanol was slowly added to the three-necked flask, the temperature was maintained at 140°C, and refluxed for 2 h to obtain a mixture of n-hexyl aluminum and n-hexanol.
[0131] The mixture of n-hexyl aluminum and n-hexanol was cooled to 80°C, and 936 g of deionized water was added thereto at a stirring speed of 120 rpm for hydrolysis. The hydrolysis time was 10 min, and a two-phase system with an upper n-hexanol phase and a lower aluminum hydroxide slurry phase was obtained. The aqueous n-hexanol phase was separated by decantation to obtain an aluminum hydroxide slurry without alcohol. The aluminum hydroxide slurry was directly spray-dried at 200°C to obtain pseudo-boehmite powder. Its characteristic parameters are shown in Table 1.
[0132] Aluminum hydroxide slurry was prepared by the same method as above, and a grain structure regulator consisting of 8 g of 2-hydroxypropionic acid and 28 g of n-hexanol was added to the aluminum hydroxide slurry. After stirring evenly, the aluminum hydroxide slurry was transferred to a stainless steel autoclave with adjustable speed mechanical stirring, and aged for 8 h at 120° C. and a stirring rate of 200 rpm. After aging, the slurry was washed with deionized water, and then placed in an oven at 120° C. for 12 h, and then ground to obtain boehmite powder. Its characteristic parameters are shown in Table 1.
[0133] (2) Preparation of aluminum hydroxide sol
[0134] Take 35g (dry basis mass of alumina) of the pseudo-boehmite powder prepared above and 65g (dry basis mass of alumina) of boehmite powder, add 264ml of 0.19mol / L nitric acid solution for peptization, then add deionized water to a total mass of 394.5g, disperse and peptize for 3 hours at a stirring rate of 300r / min to obtain an aluminum hydroxide sol with a solid content of 20wt%.
[0135] (3) Preparation of alumina balls
[0136] The aluminum hydroxide sol prepared in step (2) is dripped into the oil-ammonia column with a ball dropper. The upper layer of the oil-ammonia column is the oil phase and the lower layer is the ammonia water phase. The upper oil phase is 2 cm high n-decane and the lower ammonia water phase is 150 cm high ammonia water with a concentration of 8% by weight. The aluminum hydroxide sol is dripped into the oil layer and shrinks into a spherical shape under the action of surface tension. It passes through the interface between the oil phase and the ammonia water phase and enters the ammonia water to gel. The gelled particles are further solidified in the ammonia water phase in the lower layer of the oil-ammonia column for 4 hours to form gel beads, which are collected at the bottom of the oil-ammonia column. The obtained gel beads are taken out from the bottom of the oil-ammonia column, dried at 60°C for 3 hours and 120°C for 9 hours, and then calcined at 600°C for 6 hours to obtain γ-Al2O3 beads E, with a ball yield of 97.8% by weight.
[0137] The pore diameter distribution of γ-Al2O3 sphere E is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.
[0138] Example 6
[0139] (1) Preparation of pseudo-boehmite and boehmite
[0140] In a three-necked flask with a reflux condenser, 54 g of aluminum chips with a purity of 99.95 wt% and 180 mL (1.4 mol) of n-hexanol with a purity of 99.8 wt% were added. The reaction began after reflux at 130°C for 20 min. 724 mL (5.8 mol) of n-hexanol was slowly added to the three-necked flask, the temperature was maintained at 140°C, and refluxed for 2 h to obtain a mixture of n-hexyl aluminum and n-hexanol.
[0141] The mixture of n-hexyl aluminum and n-hexanol was cooled to 90°C, and 936g of deionized water was added thereto at a stirring speed of 120rpm for hydrolysis. The hydrolysis time was 30min, and a two-phase system with an upper n-hexanol phase and a lower aluminum hydroxide slurry phase was obtained. The n-hexanol phase of the upper layer was separated by decantation to obtain an aluminum hydroxide slurry without alcohol. The aluminum hydroxide slurry was directly spray-dried at 180°C to obtain pseudo-boehmite powder. Its characteristic parameters are shown in Table 1.
[0142] Aluminum hydroxide slurry was prepared by the same method as above, and a grain structure regulator consisting of 16g malic acid and 20g isopropanol was added to the aluminum hydroxide slurry. After stirring evenly, the aluminum hydroxide slurry was transferred to a stainless steel pressure autoclave with adjustable speed mechanical stirring, and aged for 6h at 120°C and a stirring rate of 200rpm. After aging, the slurry was washed with deionized water, and then placed in an oven at 120°C for 12h, and then ground to obtain boehmite powder. Its characteristic parameters are shown in Table 1.
[0143] (2) Preparation of aluminum hydroxide sol
[0144] Take 30g (dry basis mass of alumina) of the pseudo-boehmite powder prepared above and 70g (dry basis mass of alumina) of boehmite powder, add 261ml of 0.19mol / L nitric acid solution for peptization, then add deionized water to a total mass of 391g, disperse and peptize for 3 hours at a stirring rate of 300r / min to obtain an aluminum hydroxide sol with a solid content of 20wt%.
[0145] (3) Preparation of alumina balls
[0146] The aluminum hydroxide sol prepared in step (2) is dripped into the oil-ammonia column with a ball dropper. The upper layer of the oil-ammonia column is the oil phase, and the lower layer is the ammonia water phase. The upper oil phase is 1 cm high n-decane, and the lower ammonia water phase is 150 cm high ammonia water with a concentration of 8% by weight. The aluminum hydroxide sol is dripped into the oil layer, shrinks into a spherical shape under the action of surface tension, passes through the interface between the oil phase and the ammonia water phase, and enters the ammonia water to gel. The gelled particles are further solidified in the ammonia water phase in the lower layer of the oil-ammonia column for 2 hours to form gel beads, which are collected at the bottom of the oil-ammonia column. The obtained gel beads are taken out from the bottom of the oil-ammonia column, dried at 60°C for 3 hours, dried at 120°C for 9 hours, and then calcined at 550°C for 6 hours to obtain γ-Al2O3 beads F, with a ball yield of 96.9% by weight.
[0147] The pore diameter distribution of γ-Al2O3 pellet F is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.
[0148] Example 7
[0149] (1) Preparation of pseudo-boehmite and boehmite
[0150] In a three-necked flask with a reflux condenser, 54 g of aluminum chips with a purity of 99.95 wt% and 180 mL (1.4 mol) of n-hexanol with a purity of 99.8 wt% were added. The reaction began after reflux at 130°C for 20 min. 724 mL (5.8 mol) of n-hexanol was slowly added to the three-necked flask, the temperature was maintained at 140°C, and refluxed for 2 h to obtain a mixture of n-hexyl aluminum and n-hexanol.
[0151] The mixture of n-hexyl aluminum and n-hexanol was cooled to 90°C, and 936g of deionized water was added thereto at a stirring speed of 120rpm for hydrolysis. The hydrolysis time was 30min, and a two-phase system with an upper n-hexanol phase and a lower aluminum hydroxide slurry phase was obtained. The n-hexanol phase of the upper layer was separated by decantation to obtain an aluminum hydroxide slurry without alcohol. The aluminum hydroxide slurry was directly spray-dried at 180°C to obtain pseudo-boehmite powder. Its characteristic parameters are shown in Table 1.
[0152] Aluminum hydroxide slurry was prepared by the same method as above, and a grain structure regulator consisting of 16 g malic acid and 20 g isopropanol was added to the aluminum hydroxide slurry. After stirring evenly, the aluminum hydroxide slurry was transferred to a stainless steel autoclave with adjustable speed mechanical stirring, and aged for 8 h at 120°C and a stirring rate of 200 rpm. After aging, the slurry was washed with deionized water, and then placed in an oven at 120°C for 12 h, and then ground to obtain boehmite powder. Its characteristic parameters are shown in Table 1.
[0153] (2) Preparation of aluminum hydroxide sol
[0154] Take 35g (dry basis mass of alumina) of the pseudo-boehmite powder prepared above and 65g (dry basis mass of alumina) of boehmite powder, add 259ml of 0.19mol / L nitric acid solution for peptization, then add deionized water to a total mass of 388g, disperse and peptize for 3 hours at a stirring rate of 200r / min to obtain an aluminum hydroxide sol with a solid content of 20wt%.
[0155] (3) Preparation of alumina balls
[0156] The aluminum hydroxide sol prepared in step (2) is dripped into the oil-ammonia column with a ball dropper. The upper layer of the oil-ammonia column is the oil phase and the lower layer is the ammonia water phase. The upper oil phase is 2 cm high n-decane and the lower ammonia water phase is 150 cm high ammonia water with a concentration of 8% by weight. The aluminum hydroxide sol is dripped into the oil layer and shrinks into a spherical shape under the action of surface tension. It passes through the interface between the oil phase and the ammonia water phase and enters the ammonia water to gel. The gelled particles are further solidified in the ammonia water phase in the lower layer of the oil-ammonia column for 2 hours to form gel beads, which are collected at the bottom of the oil-ammonia column. The obtained gel beads are taken out from the bottom of the oil-ammonia column, dried at 60°C for 3 hours and 120°C for 9 hours, and then calcined at 550°C for 6 hours to obtain γ-Al2O3 beads G, with a ball yield of 97.7% by weight.
[0157] The pore diameter distribution of γ-Al2O3 ball G is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.
[0158] Example 8
[0159] (1) Preparation of pseudo-boehmite and boehmite
[0160] In a three-necked flask with a reflux condenser, 54 g of aluminum chips with a purity of 99.95 wt% and 180 mL (1.4 mol) of n-hexanol with a purity of 99.8 wt% were added. The reaction began after reflux at 130°C for 20 min. 724 mL (5.8 mol) of n-hexanol was slowly added to the three-necked flask, the temperature was maintained at 140°C, and refluxed for 2 h to obtain a mixture of n-hexyl aluminum and n-hexanol.
[0161] The mixture of n-hexyl aluminum and n-hexanol was cooled to 80°C, and 936 g of deionized water was added thereto at a stirring speed of 120 rpm for hydrolysis. The hydrolysis time was 10 min, and a two-phase system with an upper n-hexanol phase and a lower aluminum hydroxide slurry phase was obtained. The n-hexanol phase of the upper layer was separated by decantation to obtain an aluminum hydroxide slurry without alcohol. The aluminum hydroxide slurry was directly spray-dried at 200°C to obtain pseudo-boehmite powder. Its characteristic parameters are shown in Table 1.
[0162] Aluminum hydroxide slurry was prepared by the same method as above, and a grain structure regulator consisting of 12g malic acid and 20g isopropanol was added to the aluminum hydroxide slurry. After stirring evenly, the aluminum hydroxide slurry was transferred to a stainless steel autoclave with adjustable speed mechanical stirring, and aged for 10h at 120°C and a stirring rate of 200rpm. After aging, the slurry was washed with deionized water, and then placed in an oven at 120°C for 12h, and then ground to obtain boehmite powder. Its characteristic parameters are shown in Table 1.
[0163] (2) Preparation of aluminum hydroxide sol
[0164] Take 20g (dry basis mass of alumina) of the pseudo-boehmite powder and 80g (dry basis mass of alumina) of boehmite powder prepared above, add 261ml of 0.19mol / L nitric acid solution for peptization, then add deionized water to a total mass of 399g, disperse and peptize for 3 hours at a stirring rate of 300r / min to obtain an aluminum hydroxide sol with a solid content of 20wt%.
[0165] (3) Preparation of alumina balls
[0166] The aluminum hydroxide sol prepared in step (2) is dripped into the oil-ammonia column with a ball dropper. The upper layer of the oil-ammonia column is the oil phase and the lower layer is the ammonia water phase. The upper oil phase is n-octane with a height of 4 cm, and the lower ammonia water phase is ammonia water with a height of 200 cm and a concentration of 8% by weight. The aluminum hydroxide sol is dripped into the oil layer and shrinks into a sphere under the action of surface tension. It passes through the interface between the oil phase and the ammonia water phase and enters the ammonia water to gel. The gelled particles are further solidified in the ammonia water phase in the lower layer of the oil-ammonia column for 2 hours to form gel beads, which are collected at the bottom of the oil-ammonia column. The obtained gel beads are taken out from the bottom of the oil-ammonia column, dried at 60°C for 3 hours, dried at 120°C for 9 hours, and then calcined at 550°C for 6 hours to obtain γ-Al2O3 beads H, with a ball yield of 96.6% by weight.
[0167] The pore diameter distribution of γ-Al2O3 ball H is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.
[0168] Example 9
[0169] (1) Preparation of pseudo-boehmite and boehmite
[0170] In a three-necked flask with a reflux condenser, 54 g of aluminum chips with a purity of 99.95 wt% and 180 mL (1.4 mol) of n-hexanol with a purity of 99.8 wt% were added. The reaction began after reflux at 130°C for 20 min. 724 mL (5.8 mol) of n-hexanol was slowly added to the three-necked flask, the temperature was maintained at 140°C, and refluxed for 2 h to obtain a mixture of n-hexyl aluminum and n-hexanol.
[0171] The mixture of n-hexyl aluminum and n-hexanol was cooled to 90°C, and 936g of deionized water was added thereto at a stirring speed of 120rpm for hydrolysis. The hydrolysis time was 30min, and a two-phase system with an upper n-hexanol phase and a lower aluminum hydroxide slurry phase was obtained. The n-hexanol phase of the upper layer was separated by decantation to obtain an aluminum hydroxide slurry without alcohol. The aluminum hydroxide slurry was directly spray-dried at 180°C to obtain pseudo-boehmite powder. Its characteristic parameters are shown in Table 1.
[0172] Aluminum hydroxide slurry was prepared by the same method as above, and a grain structure regulator consisting of 12g malic acid and 20g isopropanol was added to the aluminum hydroxide slurry. After stirring evenly, the aluminum hydroxide slurry was transferred to a stainless steel autoclave with adjustable speed mechanical stirring, and aged for 10h at 120°C and a stirring rate of 200rpm. After aging, the slurry was washed with deionized water, and then placed in an oven at 120°C for 12h, and then ground to obtain boehmite powder. Its characteristic parameters are shown in Table 1.
[0173] (2) Preparation of aluminum hydroxide sol
[0174] Take 40g (dry basis mass of alumina) of the pseudo-boehmite powder and 60g (dry basis mass of alumina) of boehmite powder prepared above, add 259ml of 0.19mol / L nitric acid solution for peptization, then add deionized water to a total mass of 387g, disperse and peptize for 3 hours at a stirring rate of 300r / min to obtain an aluminum hydroxide sol with a solid content of 20wt%.
[0175] (3) Preparation of alumina balls
[0176] The aluminum hydroxide sol prepared in step (2) is dripped into the oil-ammonia column with a ball dropper. The upper layer of the oil-ammonia column is the oil phase, and the lower layer is the ammonia water phase. The upper oil phase is 4 cm high n-decane, and the lower ammonia water phase is 300 cm high ammonia water with a concentration of 8% by weight. The aluminum hydroxide sol is dripped into the oil layer, shrinks into a spherical shape under the action of surface tension, passes through the interface between the oil phase and the ammonia water phase, and enters the ammonia water to gel. The gelled particles are further solidified in the ammonia water phase in the lower layer of the oil-ammonia column for 2 hours to form gel balls, which are collected at the bottom of the oil-ammonia column. The obtained gel balls are taken out from the bottom of the oil-ammonia column, dried at 60°C for 3 hours, dried at 120°C for 9 hours, and then calcined at 550°C for 6 hours to obtain γ-Al2O3 balls I, with a ball yield of 98.3% by weight.
[0177] The pore diameter distribution of γ-Al2O3 pellet I is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.
[0178] Example 10
[0179] (1) Preparation of pseudo-boehmite and boehmite
[0180] In a three-necked flask with a reflux condenser, 54 g of aluminum chips with a purity of 99.95 wt% and 180 mL (1.4 mol) of n-hexanol with a purity of 99.8 wt% were added. The reaction began after reflux at 130°C for 20 min. 724 mL (5.8 mol) of n-hexanol was slowly added to the three-necked flask, the temperature was maintained at 140°C, and refluxed for 2 h to obtain a mixture of n-hexyl aluminum and n-hexanol.
[0181] The mixture of n-hexyl aluminum and n-hexanol was cooled to 90°C, and 936g of deionized water was added thereto at a stirring speed of 120rpm for hydrolysis. The hydrolysis time was 30min, and a two-phase system with an upper n-hexanol phase and a lower aluminum hydroxide slurry phase was obtained. The n-hexanol phase of the upper layer was separated by decantation to obtain an aluminum hydroxide slurry without alcohol. The aluminum hydroxide slurry was directly spray-dried at 180°C to obtain pseudo-boehmite powder. Its characteristic parameters are shown in Table 1.
[0182] Aluminum hydroxide slurry was prepared by the same method as above, and a grain structure regulator consisting of 8 g of malic acid and 20 g of isopropanol was added to the aluminum hydroxide slurry. After stirring evenly, the aluminum hydroxide slurry was transferred to a stainless steel autoclave with adjustable speed mechanical stirring, and aged for 12 hours at 120°C and a stirring rate of 200 rpm. After aging, the slurry was washed with deionized water, and then placed in an oven at 120°C for 12 hours, and then ground to obtain boehmite powder. Its characteristic parameters are shown in Table 1.
[0183] (2) Preparation of aluminum hydroxide sol
[0184] Take 25g (dry basis mass of alumina) of the pseudo-boehmite powder prepared above and 75g (dry basis mass of alumina) of boehmite powder, add 261ml of 0.19mol / L nitric acid solution for peptization, then add deionized water to a total mass of 390g, disperse and peptize for 3 hours at a stirring rate of 300r / min to obtain an aluminum hydroxide sol with a solid content of 20wt%.
[0185] (3) Preparation of alumina balls
[0186] The aluminum hydroxide sol prepared in step (2) is dripped into the oil-ammonia column with a ball dropper. The upper layer of the oil-ammonia column is the oil phase, and the lower layer is the ammonia water phase. The upper oil phase is 10 cm high n-decane, and the lower ammonia water phase is 150 cm high ammonia water with a concentration of 8% by weight. The aluminum hydroxide sol is dripped into the oil layer, shrinks into a sphere under the action of surface tension, passes through the interface between the oil phase and the ammonia water phase, and enters the ammonia water to gel. The gelled particles are further solidified in the ammonia water phase in the lower layer of the oil-ammonia column for 6 hours to form gel balls, which are collected at the bottom of the oil-ammonia column. The obtained gel balls are taken out from the bottom of the oil-ammonia column, dried at 60°C for 3 hours, dried at 120°C for 9 hours, and then calcined at 550°C for 6 hours to obtain γ-Al2O3 balls J, with a ball yield of 97.2% by weight.
[0187] The pore diameter distribution of γ-Al2O3 ball J is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.
[0188] Comparative Example 1
[0189] The method of Example 1 was followed, except that, in the preparation process of aluminum hydroxide sol, boehmite was not added, and only pseudo-boehmite was used as a raw material, specifically: 100 g (alumina dry basis mass) of pseudo-boehmite was added to 251 ml of 0.19 mol / L nitric acid solution for peptization, and then deionized water was added to a total mass of 375 g to obtain an aluminum hydroxide sol with an aluminum oxide content of 20 wt%. Finally, γ-Al2O3 spheres K were obtained, and the sphere yield was 98.9 wt%.
[0190] The pore diameter distribution of γ-Al2O3 ball K is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.
[0191] Comparative Example 2
[0192] The method of Example 1 was followed, except that in the preparation of aluminum hydroxide sol, the mass of pseudo-boehmite was 10 g (alumina dry basis mass), the mass of boehmite was 90 g (alumina dry basis mass), 269 ml of 0.19 mol / L nitric acid solution was added for peptization, and then deionized water was added to a total mass of 402 g to obtain an aluminum hydroxide sol with a solid content of 20 wt %. Finally, γ-Al2O3 spheres L were obtained, and the sphere yield was 94.3 wt %.
[0193] The pore diameter distribution of γ-Al2O3 ball L is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.
[0194] Comparative Example 3
[0195] The method of Example 1 was followed, except that no pseudo-boehmite was added during the preparation of the aluminum hydroxide sol, and only boehmite was used as a raw material, specifically: 100 g (alumina dry basis mass) of boehmite was added to 271 ml of 0.19 mol / L nitric acid solution for peptization, and then deionized water was added to a total mass of 405 g to obtain an aluminum hydroxide sol with a solid content of 20 wt%. Finally, γ-Al2O3 spheres M were obtained, and the sphere yield was 89.1 wt%.
[0196] The pore diameter distribution of γ-Al2O3 spheres M is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.
[0197] Comparative Example 4
[0198] The method of Example 1 was followed, except that no grain structure regulator was added to the aluminum hydroxide slurry during the preparation of boehmite. After being stirred evenly, the aluminum hydroxide slurry was transferred to a stainless steel autoclave and aged at 120°C for 12 hours without stirring. After aging, the slurry was washed with deionized water, then placed in an oven at 120°C for 12 hours, and then ground to obtain boehmite powder. Finally, γ-Al2O3 pellets N were obtained, and the pellet yield was 94.6% by weight.
[0199] The pore diameter distribution of γ-Al2O3 pellet N is shown in Table 2, and other physical and chemical properties such as crushing strength are shown in Table 3.
[0200] Table 1
[0201]
[0202] Table 2
[0203]
[0204]
[0205] It can be seen from Table 2 that compared with the γ-Al2O3 beads prepared in the comparative example, in the γ-Al2O3 beads provided by the present invention, pores with a diameter of 10-50 nm account for more than 80%, and pores with a diameter of 10-20 nm account for more than 60%, and pores with a diameter of 20-50 nm account for more than 10%.
[0206] Table 3
[0207]
[0208] It can be seen from Table 3 that the γ-Al2O3 pellets provided by the present invention have higher sphericity and crushing strength. The continuous reforming catalyst using the spherical alumina as a carrier is less likely to break during use, which reduces the attrition rate and prolongs the operating cycle of the catalyst.
[0209] Test Example 1
[0210] Take 50g of the γ-Al2O3 beads (A, C, H, KN) prepared in the embodiment and comparative example (based on dry alumina) as carriers, take 90g of a solution containing chloroplatinic acid, SnCl2 and hydrochloric acid as an impregnation solution, wherein the impregnation solution contains 0.29 wt% Pt, 0.3 wt% Sn and 1.2 wt% chlorine (all relative to the dry mass of the alumina carrier). The γ-Al2O3 beads A are impregnated with the impregnation solution at 25°C for a total of 4 hours, the impregnated solid is dried at 120°C for 10 hours, and then activated with water and chlorine at 510°C with air containing hydrogen chloride and water for 8 hours, wherein the molar ratio of water / HCl in the air is 50:1, and then hydrogen is introduced at this temperature for reduction for 4 hours to obtain a catalyst CatA, wherein the Pt content based on the carrier is 0.29 wt%, the Sn content is 0.3 wt%, and the Cl content is 1.1 wt%.
[0211] The catalyst was loaded in a 100 ml medium-sized evaluation device, and the catalyst reaction performance was evaluated using the refined straight-run naphtha of the composition described in Table 4 as the raw material. The evaluation conditions were: 530°C, 0.7 MPa, hydrogen / hydrocarbon volume ratio of 800 / 1, naphtha feed volume space velocity of 2 h -1 The cumulative reaction time is 120 hours. The evaluation results of each catalyst are shown in Table 5, among which C 5+ The product liquid yield and aromatics content are the average results of 120 hours of reaction, and the carbon deposit amount is the carbon deposit amount of the catalyst after 120 hours of reaction.
[0212] Table 4
[0213]
[0214] Table 5
[0215]
[0216]
[0217] It can be seen from the results in Table 5 that, compared with the comparative example, the continuous reforming catalyst obtained by using the spherical alumina provided in the embodiment of the present invention as a carrier, when applied in the continuous reforming process of naphtha, has a higher aromatics yield and a relatively low carbon deposition amount, and is suitable for use in an aromatics-type continuous reforming device.
[0218] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A spherical alumina, characterized in that: In the spherical alumina, pores with a pore diameter of 6-10 nm account for 10-22% of the total pore volume, pores with a pore diameter of 10-20 nm account for 50-75% of the total pore volume, and pores with a pore diameter of 20-50 nm account for 10-25% of the total pore volume.
2. The spherical alumina according to claim 1, wherein: In the spherical alumina, pores with a pore diameter of 6-10 nm account for 12-22% of the total pore volume, pores with a pore diameter of 10-20 nm account for 55-75% of the total pore volume, and pores with a pore diameter of 20-50 nm account for 10-20% of the total pore volume; Preferably, there are no pores with a pore diameter less than 6 nm in the spherical alumina; Preferably, in the spherical alumina, pores with a pore diameter greater than 50 nm account for less than 5% of the total pore volume.
3. The spherical alumina according to claim 1, wherein: The spherical alumina is γ-alumina; Preferably, the specific surface area of the spherical alumina is 190-230m 2 / g; Preferably, the pore volume of the spherical alumina is 0.6-0.9 cm 3 / g; Preferably, the average particle size of the spherical alumina is 1.4-1.8 mm.
4. The spherical alumina according to any one of claims 1 to 3, wherein: The sphericity of the spherical alumina is greater than 0.95; Preferably, the Q of the spherical alumina is 0.95 Greater than 95% by volume, wherein Q 0.95 is the volume proportion of spherical alumina particles with a sphericity greater than 0.95 in all spherical alumina particles; Preferably, the crushing strength of the spherical alumina is 45-80N / grain.
5. A method for preparing spherical alumina, the method comprising the following steps: (1) peptizing pseudo-boehmite and boehmite to obtain aluminum hydroxide slurry; (2) dropping aluminum hydroxide slurry into an oil-ammonia column to form wet aluminum hydroxide pellets, and then drying and calcining the wet aluminum hydroxide pellets; Wherein, the grain size of the boehmite meets: D (200) / D (002) =0.5-1.5, D (200) / D (020) =0.7-1.5, wherein the D (020) , D (200) and D (002) are the grain sizes calculated by the Scherrer formula based on the half-width of the diffraction peaks along the (020) crystal plane, (200) crystal plane and (002) crystal plane in the X-ray diffraction curve of boehmite; Among them, in the pseudo-boehmite, D (120) Less than 10 nm, wherein the D (120) is the crystallite size calculated by the Scherrer formula based on the half-peak width of the diffraction peak along the (120) crystal plane in the X-ray diffraction curve of pseudo-boehmite; Wherein, based on the total dry mass of pseudo-boehmite and boehmite, the dry mass content of pseudo-boehmite is 20-50%, and the dry mass content of boehmite is 50-80%.
6. The method according to claim 5, wherein: The grain size of the boehmite meets the following requirements: D (200) / D (002) =0.6-1.3, D (200) / D (020) =0.8-1.5; Preferably, the particle size of the boehmite is 0.1-500 μm, preferably 0.1-400 μm; Preferably, the D of the boehmite 50 It is 40-200 μm, preferably 40-100 μm.
7. The method according to claim 5, wherein: In the pseudo-boehmite, D (120) Less than 6nm; Preferably, the particle size of the pseudo-boehmite is 0.1-300 μm, preferably 0.5-200 μm; Preferably, the D of the pseudo-boehmite 50 5-60 μm, preferably 30-60 μm.
8. The method according to any one of claims 5 to 7, wherein: Based on the total dry mass of pseudo-boehmite and boehmite, the dry mass content of pseudo-boehmite is 20-40%, and the dry mass content of boehmite is 60-80%; Preferably, the acid used for the peptization in step (1) is an inorganic acid and / or an organic acid, the inorganic acid is nitric acid and / or hydrochloric acid, and the organic acid is at least one selected from trichloroacetic acid, formic acid and citric acid; Preferably, the ratio of the mass of the acid used for peptization in step (1) to the total mass of pseudo-boehmite and boehmite calculated as alumina is 0.01-0.1; Preferably, the acid used for the peptization in step (1) is provided in the form of an acid solution, and the concentration of the acid solution is 0.1-2 mol / L; Preferably, the aluminum hydroxide slurry obtained in step (1) has a solid content of 15-28% by weight.
9. The method according to any one of claims 5 to 8, wherein: The oil-ammonia column comprises an organic phase and an ammonia aqueous phase, and the height ratio of the organic phase to the ammonia aqueous phase is 1:5-300; Preferably, the organic phase is C5-C 20 Alkanes, preferably at least one selected from gasoline, kerosene, petroleum ether, n-pentane, n-hexane, n-heptane, n-octane, n-decane and undecane; Preferably, the concentration of the aqueous ammonia is 6-18% by weight; Preferably, the calcination conditions in step (2) include: a temperature of 450-800° C. and a time of 2-8 hours.
10. Use of the spherical alumina described in any one of claims 1 to 4 or the spherical alumina prepared by the method described in any one of claims 5 to 9 in catalyst preparation, preferably in continuous reforming catalyst preparation.
Citation Information
Patent Citations
Alumina carrier as well as catalyst and application
CN104148117A
Preparation method for alumina pellet with bimodal pore distribution, alumina pellet and catalytic reforming catalyst
CN107837797A
Alumina pellet carrier and preparation method thereof, and catalytic reforming catalyst
CN107837798A
Aluminum oxide as well as preparation method and application thereof
CN111744483A
Blocky grain boehmite and preparation method thereof
CN112678856A
Cited By
High-purity spherical alumina and method for producing the same
CN122877779A